Boot camp: Training and dressing regimens for modeling plantar wounds in the swine. (February 2023) - Stalnaker, Katherine J; Fuchs, Christiane; Slate, Andrea; Camacho, Jennifer N; Pham, Linh; Wang, Ying; Anderson, R Rox; Tam, Joshua
Foot ulceration annually affects millions of patients and accounts for billions of dollars in medical expenses in the US alone. Many previous studies have investigated co-morbidities associated with impaired healing, such as microbial infection, compromised circulation, and diabetes. By comparison, little is known about how wound healing proceeds in plantar skin, despite its many unique specializations related to its load-bearing function. One of the main challenges in modeling plantar wounds is the difficulty in maintaining wound dressings, as animals generally have a low tolerance to wearing bandages on their feet. With assistance from the MGH Center for Comparative Medicine, we developed a positive reinforcement-based behavioral training regimen that successfully induced tolerance for plantar dressings in swine, which is a critical first step towards enabling in vivo study of the wound healing process in this highly specialized skin area. This training program will be described in detail in this manuscript.